Genetic biomarkers for intravenous immunoglobulin response in chronic inflammatory demyelinating polyradiculoneuropathy. (6th February 2021) - Kuitwaard, Krista; van Doorn, Pieter A.; Bengrine, Thiziri; van Rijs, Wouter; Baas, Frank; Nagelkerke, Sietse Q.; Kuijpers, Taco W.; Fokkink, Willem‐Jan R.; Bunschoten, Carina; Broers, Merel C.; Willemsen, Sten P.; Jacobs, Bart C.; et al.
Abstract: Background and purpose: Chronic inflammatory demyelinating polyradiculoneuropathy (CIDP) is a clinical and electrophysiological heterogeneous immune‐mediated polyneuropathy. Intravenous immunoglobulin (IVIg), corticosteroids, and plasma exchange are proven effective treatments for CIDP. The clinical response to IVIg is variable between patients and currently unexplained. Finding biomarkers related to treatment response can help to understand the diversity of CIDP and personalise treatment choice. Methods: We investigated whether genetic variation between patients may explain some of these differences in treatment response. Based on previous publications, we selected six candidate genes that might affect immune and axonal functions, IVIg metabolism, and treatment response in CIDP. Genetic variants were assessed in 172 CIDP patients treated with at least one course of IVIg (2 g/kg). A response to IVIg was defined by ≥1 grade improvement on the modified Rankin Scale. Blood samples were tested for variations in CNTN2, PRF1, FCGRT, FCGR2B, GJB1, and SH2D2A genes. Results: In univariate analysis, patients with the FCGR2B promoter variant 2B.4/2B.1 responded more often to IVIg than patients with the 2B.1/2B.1 variant (odds ratio [OR] = 6.9, 95% confidence interval [CI] = 1.6–30; p  = 0.003). Patients with the p.(Ala91Val) variant of PRF1 were less often IVIg responsive (OR = 0.34, 95% CI = 0.13–0.91; p  = 0.038). In multivariate analysis, both PRF1 and FCGR2B showed discriminative ability to predict the chance of IVIg response (area under the curve = 0.67). Conclusions: Variations in PRF1 and the promoter region of FCGR2B are associated with the response to IVIg in CIDP. These findings, which require validation, are a first step towards the understanding of the heterogeneity in the treatment response in CIDP. Abstract : We investigated whether genetic variation in six candidate genes was associated with the response to IVIg in CIDP patients. Variations in PRF1 and the promoter region of FCGR2B were associated with the response to IVIg in CIDP.